2021
DOI: 10.3389/fnagi.2021.735334
|View full text |Cite
|
Sign up to set email alerts
|

Microdissected Pyramidal Cell Proteomics of Alzheimer Brain Reveals Alterations in Creatine Kinase B-Type, 14-3-3-γ, and Heat Shock Cognate 71

Abstract: Novel insights on proteins involved in Alzheimer’s disease (AD) are needed. Since multiple cell types and matrix components are altered in AD, bulk analysis of brain tissue maybe difficult to interpret. In the current study, we isolated pyramidal cells from the cornu ammonis 1 (CA1) region of the hippocampus from five AD and five neurologically healthy donors using laser capture microdissection (LCM). The samples were analyzed by proteomics using 18O-labeled internal standard and nano-high-performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…In contrast to earlier studies, we did not observe CKB expression in inhibitory neurons (Burbaeva et al, 1992;Lowe et al, 2013;Yoshimine et al, 1983) nor did we observe CKB-ir cells that do not co-stain for astrocyte markers. However, our results cannot completely rule out expression of CKB in neurons, as previous single nuclei transcriptomic (Hodge et al, 2019) and single cell mass spectrometry (Sandebring-Matton et al, 2021) studies have identified CKB in neurons. These discrepancies might be due to differences in CKB translation, intercellular transport, or post translational state of CKB in neurons and astrocytes.…”
Section: Discussioncontrasting
confidence: 82%
“…In contrast to earlier studies, we did not observe CKB expression in inhibitory neurons (Burbaeva et al, 1992;Lowe et al, 2013;Yoshimine et al, 1983) nor did we observe CKB-ir cells that do not co-stain for astrocyte markers. However, our results cannot completely rule out expression of CKB in neurons, as previous single nuclei transcriptomic (Hodge et al, 2019) and single cell mass spectrometry (Sandebring-Matton et al, 2021) studies have identified CKB in neurons. These discrepancies might be due to differences in CKB translation, intercellular transport, or post translational state of CKB in neurons and astrocytes.…”
Section: Discussioncontrasting
confidence: 82%
“…Deparaffinization and antigen retrieval of the brain tissue sections were performed as previously described. 30 After washing with phosphate-buffered saline (PBS), sections were blocked in 0.1% Triton X-100 (Sigma-Aldrich), 2% normal goat serum (Thermo Fisher Scientific, MA, USA) and 1% bovine serum albumin (Sigma-Aldrich) in PBS for 1 h at room temperature. Sections were then incubated with primary antibodies diluted in blocking buffer overnight at +4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In subcellular regions where energy is being rapidly consumed (e.g., surrounding ATPases), CKB transfers the phosphate group from phosphocreatine to ADP, increasing local concentrations of ATP . The role of CKB in the creatine/phosphocreatine cycle has been studied in various tissues, and dysregulation of CKB via mutations, oxidation, or abundance alterations is associated with several disease states, including Alzheimer’s and Huntington’s diseases, and cancer metastases. , However, the contribution of CKB to xenobiotic biotransformation remains underexplored, as most studies have only investigated the contribution of CKM. …”
mentioning
confidence: 99%